Influence of the second stage of labor on maternal and neonatal outcomes in vaginal births after caesarean section: a multicenter study in Germany - G. Gitas; L. Proppe; A. K. Ertan; S. Baum; A. Rody; M. Kocaer; K. Dinas; L. Allahqoli; A. S. Laganà; A. Sotiriadis; S. Sommer; I. Alkatout (BMC, 2021)
Abstract Background The American College of Obstetricians and Gynecologists (ACOG) introduced a new standard of care in 2014, extending the duration of the second stage of labor in order to reduce caesarean delivery (CD) rates and its severe complications. The aim of the present study is to evaluate success rates of trial of labor after caesarean section (TOLAC), as well as maternal and neonatal outcomes after the establishment of the recent guidelines. Methods A retrospective study was performed at two large departments in Germany from January 2008 to January 2018. Patients undergoing TOLAC were divided into two groups. Group I (958 patients) was constituted before the establishment of the current guidelines, and Group II (588 patients) after the establishment of the guidelines. A subgroup analysis was performed to compare neonatal outcomes after successful TOLAC and operative vaginal delivery with those after failed TOLAC and secondary CD. Results The success rate of vaginal births after cesarean section (VBAC) fell from 66.4% in Group I to 55.8% in Group II (p < 0.001). The median duration of the second stage of labor was statistically significantly longer in Group II than in Group I (79.3 ± 61.9 vs. 69.3 ± 58.2 min) for patients without previous vaginal birth. The incidence of operative vaginal delivery decreased from Group I to Group II (9.6% vs. 6.8%). The incidence of third- and fourth-degree perineal lacerations, blood loss and emergency CD were similar in the two groups. Concerning the neonatal outcome, our groups did not differ significantly in regard of rates of umbilical artery cord pH < 7.1 (p = 0.108), the 5-min Apgar scores below 7 (p = 0.224) and intubation (p = 0.547). However, the transfer rates to the neonatal care unit were significantly higher in Group II than in Group I (p < 0.001). Neonatal outcomes did not differ significantly in the subgroup analysis. Conclusion Extending the second stage of labor does not necessarily result in more vaginal births after TOLAC. Maternal and neonatal outcomes were similar in both groups. Further studies will be needed to evaluate the role of operative vaginal delivery and the duration of the second stage of labor in TOLAC.